2021
DOI: 10.48550/arxiv.2110.03521
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The missing label of $\mathfrak{su}_3$ and its symmetry

Abstract: We present explicit formulas for the operators providing missing labels for the tensor product of two irreducible representations of su 3 . The result is seen as a particular representation of the diagonal centraliser of su 3 through a pair of tridiagonal matrices. Using these explicit formulas, we investigate the symmetry of this missing label problem and we find a symmetry group of order 144 larger than what can be expected from the natural symmetries. Several realisations of this symmetry group are given, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A specific example would be to consider SU (3), to determine if similar tangle diagrams are also associated to natural elements of the centralizers of U q (su 3 ) in its tensor products, and to look if the approach using tangles and partial traces allows to understand better the algebra formed by these elements. The study of the algebraic structure of the centralizer of U (su 3 ) has been initiated in [10,11]. It could also be interesting to examine how the choice of a different manifold for the CS action affects the results of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…A specific example would be to consider SU (3), to determine if similar tangle diagrams are also associated to natural elements of the centralizers of U q (su 3 ) in its tensor products, and to look if the approach using tangles and partial traces allows to understand better the algebra formed by these elements. The study of the algebraic structure of the centralizer of U (su 3 ) has been initiated in [10,11]. It could also be interesting to examine how the choice of a different manifold for the CS action affects the results of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Remark 2. With an appropriate identification of parameters, it can be shown that the matrix elements of x and y have the same form as those of the missing label operators in the two fold tensor product of su(3) found in [12].…”
Section: The Operators X and Y In The Bargmann-moshinsky Basismentioning
confidence: 91%
“…ii. the determination in [12] with the nested Bethe ansatz of the eigenvalues of an operator providing the missing label in the SU (3) Clebsch-Gordan problem.…”
Section: Introductionmentioning
confidence: 99%